2009
DOI: 10.1007/s10600-009-9414-y
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds from several Polygonum species

Abstract: 615.43The genus Polygonum L. (Polygonaceae) is represented in the flora of Siberia by 23 species that are used to treat inflammatory diseases of the kidneys and gastrointestinal tract. P. aviculare, the herb of which is used for diseases of the lymphatic system and kidney-stone illness and as a tonic and hemostatic agent, has been described in Tibetan medicine under the name "bri-ta-sa-dzin." The Tibetan name "nya-lo" corresponds to the species P. divaricatum and P. amphibium L. [1,2]. The herb and roots of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…These mismatches may be explained as the analyses were performed with simpler HPLC instruments and the identification of compounds was mainly based on their retention times that might sometimes lead to incorrect identification of analytes. The other issue is that at least several reports existing in the literature describe the occurrence of flavone glycosides (mainly apigenin and luteolin derivaties) in the herb of P. aviculare (Kawasaki et al, ; Sun et al, ; Nikolaeva et al, ). The presence of those compounds was confirmed neither in the previous study (Granica et al, ) nor in the present paper.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These mismatches may be explained as the analyses were performed with simpler HPLC instruments and the identification of compounds was mainly based on their retention times that might sometimes lead to incorrect identification of analytes. The other issue is that at least several reports existing in the literature describe the occurrence of flavone glycosides (mainly apigenin and luteolin derivaties) in the herb of P. aviculare (Kawasaki et al, ; Sun et al, ; Nikolaeva et al, ). The presence of those compounds was confirmed neither in the previous study (Granica et al, ) nor in the present paper.…”
Section: Resultsmentioning
confidence: 99%
“…Most available textbooks and scientific papers report that Polygonum aviculare herb contains mucilage, tannins, silicic acid derivatives and flavonoids as dominating compounds. Among the flavonoids, quercetin, kaempferol and myricetin glycosides are mentioned with avicularin as major flavonoid constituents occurring in aerial parts (Hansel et al, ; Smolarz, ; Wichtl, ; Nikolaeva et al, ; Nugroho et al, ). Recent studies confirmed that common knotgrass contains flavonoids as major compounds and that the presence of most had not previously been reported (Granica et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other phenolic compounds, such as phenolcarboxylic and hydroxycinnamic acids derivatives, could be observed (Kurkin, 2003;Gómez-Romero et al 2010). P. acuminatum showed the poorest number of phenolic compounds, which are mainly composed by phenolcarboxylic acids derivatives (Nikolaeva et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we communicate for the first time results from chromatographic analysis of the amino-and fatty-acid (FA) compositions of the aerial part of Polygonum minus collected in Talgar Gorge, Almaty District. Only the flavonoid composition of this species was studied earlier [3].Herb of P. minus was extracted with EtOH (50%, 1:7 plant-extractant ratio) at 76-78°C for 1 h. The resulting extract was concentrated to dryness at 50°C and <1 atm [4]. Free amino acids in the aqueous EtOH extract were determined on a Carlo Erba 4200 GC.…”
mentioning
confidence: 99%
“…Herein, we communicate for the first time results from chromatographic analysis of the amino-and fatty-acid (FA) compositions of the aerial part of Polygonum minus collected in Talgar Gorge, Almaty District. Only the flavonoid composition of this species was studied earlier [3].…”
mentioning
confidence: 99%